Is Turnover Intention of Waste Industry Employees Determined by Career Growth, Affective, Normative and Continuance? - Rahmawati, Anik; Havidz, Ikramina Larasati Hazrati; Cahyadi, Ihlas (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
However, in some businesses, job requirements are sometimes not in line with employees' aspirations for professional advancement, which often leads to a high incidence of employee turnover. The goal of this study is to determine how the likelihood of employee turnover is influenced by career development, emotional commitment, normative commitment, and continuation commitment.Purposive sampling was also utilised in this study to choose respondents. 158 employees, primarily on the island of Java, who work in the waste business industry were the subject of this study. The data is examined using the structural equation model (SEM) technique. According to the study's findings, career growth positively and significantly influences commitment, continuance commitment, and normative commitment. Additionally, career growth, affective commitment, normative commitment, and continuance commitment do not influence turnover intention. Last but not least, psychological capital does not moderate the relationship between affective commitment and turnover intention.